PENGARUH MOTIVASI KERJA, KEPUASAN KERJA DAN BUDAYA KERJA TERHADAP KINERJA DOSEN TETAP PADA FAKULTAS TEKNOLOGI INDUSTRI UNIVERSITAS TRISAKTI - Sonny Sugiarto; Stephanus Zaldy Gunawan; Sofia Maulida (Sekolah Tinggi Ilmu Ekonomi Bisnis Indonesia, 2022)
This research aims to know the influence of job motivation, job satisfaction and job culture on performance lecturer remains on Fakultas Teknologi Industri Universitas Trisakti. This research aims to know the influence of job motivation, job satisfaction and job culture on performance lecturer anyway. The research of using primary data obtained from a questionnaire that was distributed from the respondent who is a Professor of structural/functional non permanent Fakultas Teknologi Industri Universitas Trisakti. The questionnaires are distributed 75 questionnaires using the sample slovin formula be 63 used and well stocked by the respondents which processed using SPSS statistics software assistance 22.0 for Windows to be tested the validity, reliability, heteroskedastisitas, autocorrelation, multicollinearity, multiple linear regression, t-test, F-test and a test of the determination of the coefficient to determine the influence of each variable.